(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Contemporary Serbian drama is marked by female authors’ sensibility, which is demonstrated not only by the presence of women writers such as Biljana Srbljanović, Milena Marković, Maja Pelević, Milena Bogavac etc., but also by the change in discourse and form of dramatic text. These changes are most visible in Milena Marković’s plays: fragmentariness, lyricism, performance exhibitionism, and cabaret-like scenes of historical drama. Feminist theory, criticism and philosophy, especially the utopian idealism and the radical language of cyber feminists (Donna Haraway), as well as the post-feminists’ self-questioning (Judith Butler), are used as a platform for interpreting Milena Marković’s texts.